O papel da finalidade imanente da ação humana na ética e na política de Spinoza - Gomes, Carlos Wagner Benevides (2021)
The seventeenth-century Dutch philosopher Benedictus de Spinoza built ontologically, in his great work Ethics, a practical philosophy aimed at knowing the causes and the exercise of human liberty, seeking to achieve beatitude or happiness, which consists in the intellectual love of God. Defending a plan of immanence, the reality of which would be self-production, Spinoza sought to rid man of certain prejudices, such as finalism, as rigorously denounced in the appendix to Part I of Ethics. For Spinoza, God or Nature doesn’t exist or act as a final and transitive cause, but as an efficient and immanent cause, since there is only the necessary and nothing contingent. This would be criticism of the transcendent or divine finality. But knowing that man is a finite mode of this God and is subject to thinking and acting according ends, would he be led by an immanent finality when he seeks only what is useful to his nature and nothing more? What role would this immanent finality play in the ethical and political realization? As Spinoza will say in Definition 7 of Part IV of Ethics, the end will have a resignification: far from being a final and transcendent cause, it is an efficient cause, being our own appetite. Appetite is also understood as Desire, which is man's own essence in what determines his action, according to Definition 1 of the Affects of Part III of Ethics. An internal activity of its own appetite, human finality would have a mobilizing function in ethics and politics whose power is to seek the freedom and happiness of the individual and the collective. Moreover, how can we deduce a function of the immanent human finality in ethics and politics even in an antifinalist ontology? Such questions will problematize and guide the research. Therefore, this thesis aims to clarify the role of the immanent finality of human action in ethics and politics from the approach and reading of the following works: Ethics, Theological-Political Treatise, Political Treatise among other writings. To do so, we will take as a starting point the relationship between concepts and definitions in the Ethics of Effort (conatus) or individual's power to persevere in existence and End (finis), which is the Appetite (appetitus) or Desire (cupiditas) human being in search of what is useful to his nature, such as liberty and happiness as ethical ends. Futhermore, we will see how this immanent finality develops in the political field, especially when man establishes as immanent ends to a state (the democratic), civil freedom, peace and security.